Persisting Motor Function Problems in School-Aged Survivors of Congenital Diaphragmatic Hernia - de Munck, Sophie; van der Cammen-van Zijp, Monique H. M.; Zanen-van den Adel, Tabitha P. L.; Wijnen, René M. H.; Cochius-den Otter, Suzan C. M.; van Haren, Neeltje E. M.; Gischler, Saskia J.; van Rosmalen, Joost; IJsselstijn, Hanneke (Frontiers in Pediatrics, 2021)
Background and objectives Children born with congenital diaphragmatic hernia (CDH) and treated with extracorporeal membrane oxygenation (ECMO), are at risk for motor function impairment during childhood. We hypothesized that all children born with CDH are at risk for persistent motor function impairment, irrespective of ECMO-treatment. We longitudinally assessed these children’s motor function. Methods Children with CDH with and without ECMO-treatment, born 1999-2007, who joined our structural prospective follow-up program were assessed with the Movement Assessment Battery for Children (M-ABC) at 5, 8, 12 years. Z-scores were used in a general linear model for longitudinal analysis. Results We included 55 children, of whom 25 had been treated with ECMO. Forty-three (78%) were evaluated at three ages. Estimated mean (95% CI) z-scores from the general linear model were -0.67 (-0.96 to -0.39) at 5 years of age, -0.35 (-0.65 to -0.05) at 8 years, and -0.46 (-0.76 to -0.17) at 12 years. The 5- and 8-years scores differed significantly (p=0.02). Motor development was significantly below the norm in non-ECMO treated patients at five years; -0.44 (-0.83 to -0.05), and at all ages in the ECMO-treated-patients: -0.90 (-1.32 to -0.49), -0.45 (-0.90 to -0.02) and -0.75 (-1.2 to -0.34) at 5, 8 and 12 years, respectively. Length of hospital stay was negatively associated with estimated total z-score M-ABC (p=0.004 multivariate analysis). Conclusion School-age children born with CDH are at risk for motor function impairment, which persists in those who received ECMO-treatment. Especially for them long-term follow up is recommended.